Individual differences in the early recognition of moral information in lexical processing: An event-related potential study - Qun Yang (Nature Portfolio, 2017)
Abstract Previous studies have shown that intuitive moral cognition occurs at an early stage. However, inconsistent findings indicate that moral information is recognized at a relatively late stage. This study uses the recognition potential (RP) as a neural index and simultaneously measures individuals’ moral preferences using the Moral Foundation Questionnaire. We aim to investigate how individual differences in moral preferences modulate the processing of morality in the pre-semantic stage and provide some insights to explain the variation in rapid information processing linked to morality. The participants performed an implicit task in which recognizable words depicting geographical names or behaviors related to moral, disgusting or neutral content alternated with background stimuli at high rates of presentation. The results showed that the early recognition of moral information manifested in the RP depended on an individual’s moral concerns. Participants with a higher level of endorsement of the harm/care foundation exhibited a greater net moral effect, namely, greater mean amplitudes of the moral-neutral RP difference waves. Meanwhile, only the group that was more sensitive to the harm/care foundation showed a distinctively larger RP for the moral words than for the neutral words. Overall, these findings suggest that the early processing of moral cognition may hinge on individual differences in moral concerns about other people’s suffering.